Taiwan IP court decisions tend to treat likelihood of confusion and likelihood of dilution as mutually interchangeable - LIU, Kung-chung (Institutional Knowledge at Singapore Management University, 2019)
The Taiwan Intellectual Property Court (IP Court) ruled in its capacity as the first instance court that the well-known trademark and the alleged infringing trademark at dispute were not the same or similar, and therefore neither likelihood of confusion nor dilution of the plaintiff’s well-known trademark occurred. The IP Court further found that the defendant has not been “knowingly using words contained in another person’s well-known registered trademark as the name of a company”, because the allegedly infringing corporate name was not exactly the same Chinese characters as the well-known trademark. The plaintiff appealed the case to the appellate instance of the IP Court which sustained the appeal and revoked the decision. The case is still pending before the Supreme Court.